Practices and Barriers in Sexual History Taking: A Cross-Sectional Study in a Public Adult Primary Care Clinic. Issue 8 (28th June 2020) - Palaiodimos, Leonidas; Herman, Heather S.; Wood, Erika; Karamanis, Dimitrios; Martinez-Rodriguez, Cesar; Sanchez-Lopez, Alejandra; Ruderman, Emma; Jang, Maximus; Fischer, Daniel; Huang, Hao; Gadde, Uttara; Leider, Jason
Abstract: Background: Surveys report low frequencies of sexual history (SH) obtained in primary care. Sexually transmitted infections incidence can be reduced with timely screening. It is important to determine whether providers obtain thorough SH and to identify needs for improvement. Aim: To evaluate the frequency and depth of SH taking in primary care. Methods: In this cross-sectional cohort study, 1, 017 primary care visits were reviewed (1, 017 adult patients, female 55.26%). 417 patients were seen by male providers and 600 patients were seen by female providers. Multivariate ordered and logit models were deployed. Main Outcome Measures: The primary outcome measures included SH taking rates and completeness based on the 5 P model as described by the Centers for Disease Control and Prevention. Results: All components of SH were explored in 1.08% of visits. Partial SH was obtained in 33.92% of visits. No SH was taken in the majority of visits (65%). SH was more likely to be taken from female patients than from male patients ( P < .001), and was less likely to be obtained from older patients as compared to younger individuals ( P < .001). There was no significant difference in SH taking between male and female providers ( P = .753). The provider title and the level of training were found to be independent predictors of SH taking ( P < .001). Clinical Implications: The results of this study highlight an unmet need for more comprehensive and consistent SH taking amongst providers, particularly in high-risk settings, so that SH can be used as a valuable tool in preventive care. Strengths & Limitations: To the best of our knowledge, this is the largest study to date examining SH taking in the primary care setting. Limitations include the retrospective study design, lack of generalizability to other hospitals, and inconsistencies in available data. Conclusion: The SH taking rates in primary care clinics are globally low with a variation depending on the provider position or level of training, provider gender, and patient age.